Design Thinking for Sustainable Development - Zeltina , Mara (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The complexity of environmental and sustainability challenges has created an ongoing need for innovative and integrated approaches to address them. Design disciplines have a long history. The method “design thinking”, originally applied in architecture, engineering and business, has led to new and creative problem solving, thus creating much potential for use in sustainable development planning. While principles of good design are well established, there has been limited integration of design thinking with environmental science, sustainable development planning and education. This research was focused on how a sustainability approach can be merged with design thinking to develop socially responsible and environmentally sustainable products and services. The case study has been carried out in the master’s study course Sustainable Development Planning. Some of basic principles and stages of design thinking, such as empathy, creativity, collaboration, responsibility and interdisciplinary approach have been tested by using students project work evaluation regarding certain criteria and survey after the study course. The first results of approbated design thinking principles and methods, significant advantages and disadvantages and the perspective of using this method have been analysed and discussed. As the result from this study proposals for the improvement of the content of this study course and related study courses (a study course on sustainable development issues is compulsory in all undergraduate study programs in Latvia) and for the specification of test tasks have been developed, considering also future needs to provide the study course remotely.